(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The years 2020 and 2021 will be known with the panic threat to human life because of COVID19 and huge numbers of casualties are going on globally including in India. Millions of people have been infected with the Corona Virus, and thousands of people have died as a result. Some of the world’s most powerful nations, such as Italy and the United States, have been severely impacted, with more than 500 lives lost every day. Corona has wreaked havoc on the global economy, enslaving countries such as India, France, Germany, Spain, and Iran. This crippling disease has wreaked havoc across the globe. Since there is yet to be a remedy, after the lockout restrictions are removed, it is essential to ensure that social distancing is exercised at the locations. Countries like India, where less number of cases were registered during the targeted lockout, have seen an increase in cases since the restrictions were lifted. The study focuses on the implementation of a social distancing framework that keeps track of the distance between people in real time using specialized libraries available for real-time implementations. The presented work proposes the use of open source hardware with the integration of OpenCV so that the real time analysis of social distancing can be done. OpenCV is free and open source framework for image and video processing with the flavor of Artificial Intelligence and is presented in this manuscript.